저압가스질화에서 탄소강의 초기 화합물층 형성 거동 - 김윤기(Yoon-Kee Kim); 김상권(Sang Gweon Kim) (Biuletyn Uniejowski, 2011)
Growth behaviors of iron-nitride on S45C steels at low pressure gas nitriding were examined. Surfaces of the steels covered with fine and porous oxide during the pre-oxidation using $N_2O$ gas. Well faceted particles connected with them were observed after 1 min nitriding. They grew steadily and filled inter-pores during additional nitriding process. From the X-ray diffraction analysis, ${γ}'$-iron nitride was dominantly formed at the initial stage but the amount of ${ε}$-iron nitride was rapidly increased as nitriding treatment time. The porous layer was formed on the particles and thickened up to half of nitride layer after 60 min nitriding. The observed growth behaviors were discussed in internal stress related with volume expansion involved in transforming from iron to iron-nitrides.